Wallets, Ballots, or Bullets: Does Wealth, Democracy, or Military Capabilities Determine War Outcomes? - HENDERSON, ERROL A.; BAYER, REŞAT (International Studies Quarterly, 2013)
We examine the extent to which wealth, democracy, and/or relative military capabilities contribute to victory in interstate war. Examining contingency tables, we find that states with greater military capabilities are more likely to win their wars whether they are wealthier or democratic, and democratic states perform marginally better than wealthier states in war. Probit analyses indicate that although each of the variables has a robust and positive impact on war victory, relative capabilities has the strongest substantive impact, followed by wealth, then democracy. Hazard analyses reveal that states with greater military capabilities fight shorter wars than either democracies or wealthier states, and controlling for capabilities and wealth, the relationship between democracy and war duration is not significant, which challenges the view that democracies have a unique propensity to fight shorter wars. We also find that the democratic victory phenomenon is not universal, but is contingent on the placement of a single country, Israel, in the Western or non-Western democracy category. In sum, our analyses indicate that although each of the three factors contributes to war victory, relative military capability is the most powerful, consistent, and robust predictor to victory in interstate war.